LEGITIMASI PENJARA ADAT NAGARI TERHADAP TINDAK PIDANA ASUSILA (Studi Kasus Nagari Tigo Jangko, Kec. Lintau Buo, Kab Tanah Datar) - Tanjung, Faisal (UNES Journal of Swara Justisia, 2019)
Based on the results of the study concluded that First, the application of traditional nagariprisons in the enforcement of customary criminal law in Nagari Tigo Jangko there areseveral stages which consist of being caught being immoral, they are escorted to thenagari guardian's office. The male perpetrator was put into Nagari Prison which waslocated next to the Nagari guardian's office, while the female was put into the Nagariguardian's office. In Nagari Prison the perpetrators are shown to the public(approximately 3-5 hours). In the span of a few hours, Ninik Mamak the perpetrator,religious leader, adat and nagari apparatus held a meeting in adat density to determinethe customary punishment that could be imposed on the perpetrator. Then the perpetratorswere taken by the police to the Lintau Buo Sub-district Police Station located in Pangian,if there was a criminal element in it (National Criminal Law). Second, the legitimacy of theNagari Tigo Jangko customary prison against immoral crime is a strategic role inregulating the implementation of the nagari government. The customary prison in NagariTigo JangÂ¬ko has been regulated in the local nagari regulations and has the agreement ofthe customary and youth stakeholders, in the event that the relevant violations will first beconvened at the Nagari Indigenous Peoples Office by nagari and pucuk leaders localcustoms and if found a committed violation fined customarily and put in a customaryofficer for one day or before the hearing in KAN is finished, if the perpetrator's actionthere is an element of criminal offense, the perpetrator will be handed over to the Polsek,but the offender is not fined by custom.